2020
DOI: 10.26717/bjstr.2020.27.004518
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coronavirus (COVID-19) Treatment Options

Abstract: Corona virus also called SARS-COV-2 showed highly pathogenic, caused severe or even life-threatening diseases, and still transmitted from person-to-person. Given fast evolution of the COVID-19 outbreak, world health organization declared its outbreak as pandemic. Until now, no drugs or biologics have been proven to be effective for the prevention or treatment of COVID-19. Mainstream medicine has little in its arsenal for viral diseases. Some promising agents are selectively RNA inhibitors, an antimalarial agen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…A recent study has revealed the role gender plays in morbidity and mortality of SARS-CoV-2 infection (Drosten et al, 2003). Studies pondering the mechanistic aspect for infectivity suggest that males have high concentration of circulating angiotensin-converting enzyme 2 (ACE2) than in their female counterpart (Patel, Velkoska, & Burrell, 2013;Ullah, 2020a). ACE2 is the targeting receptor site for the (SARS-CoV) and the associated human respiratory coronavirus NL63, that exhibit in human airway epithelia and lung parenchyma (Jia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has revealed the role gender plays in morbidity and mortality of SARS-CoV-2 infection (Drosten et al, 2003). Studies pondering the mechanistic aspect for infectivity suggest that males have high concentration of circulating angiotensin-converting enzyme 2 (ACE2) than in their female counterpart (Patel, Velkoska, & Burrell, 2013;Ullah, 2020a). ACE2 is the targeting receptor site for the (SARS-CoV) and the associated human respiratory coronavirus NL63, that exhibit in human airway epithelia and lung parenchyma (Jia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin receptor blockers (ARBs) have effects that are parallel to angiotensin converting enzyme (ACE) inhibitors, however ACE inhibitors act by inhibiting the development of angiotensin II instead of blocking the binding of angiotensin II to muscles on blood vessels (Jia et al, 2005;Ullah, 2020b). ARBs are used for regulating high blood pressure, to treat heart failure, and restrain kidney failure in individuals with diabetes (Ullah, 2020a;Xie et al, 2020). Hence, angiotensin receptor blockers (ARBs such as losartan, valsartan, telmisartan, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In the past 1 year, mesenchymal stem cell (MSCs) therapy for SARS-CoV-2 infection is being explored in multiple studies. 135 , 136 MSCs have unique potential for immunomodulation, antiviral defense, and tissue regeneration. Umbilical cord-derived MSCs have shown promising results in smaller studies.…”
Section: Evs In the Treatment Of Lung Diseases Including Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2) Infectionmentioning
confidence: 99%
“… 150 , 151 Preliminary studies suggest that co-treatment with EVs obtained from mesenchymal cell secretomes is effective in treating COVID-19 patients. 135 , 136 , 151 Further preclinical data considering safety, ethics, and practicality is needed to adapt this regimen for COVID-19 treatment.…”
Section: Evs In the Treatment Of Lung Diseases Including Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2) Infectionmentioning
confidence: 99%
“…Particles with positive charges, known as free radicals, engulf electrons from healthy cells to neutralize their own charge, causing cellular damage [ 15 , 58 , 59 ]. In contrast, negatively charged bubbles fight free radicals to improve the health of damaged cells and detoxify the inflammatory fluids in diseased tissue [ 15 , 60 ].…”
Section: Technology and Microbubblesmentioning
confidence: 99%